2022
DOI: 10.1038/s41380-022-01632-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective visuoconstructional impairment following mild COVID-19 with inflammatory and neuroimaging correlation findings

Abstract: People recovered from COVID-19 may still present complications including respiratory and neurological sequelae. In other viral infections, cognitive impairment occurs due to brain damage or dysfunction caused by vascular lesions and inflammatory processes. Persistent cognitive impairment compromises daily activities and psychosocial adaptation. Some level of neurological and psychiatric consequences were expected and described in severe cases of COVID-19. However, it is debatable whether neuropsychiatric compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…14 A prospective observational cohort study of individuals with polymerase chain reaction (PCR) confirmed SARS-CoV-2 infection and mild COVID-19 presentation examined neurological impairment four months after infection using neuropsychological, ocular, and neurological tests, immune marker assays, structural magnetic resonance imaging (MRI), and 18 FDG-PET neuroimaging. 15 In approximately 25% of individuals, a specific vasoconstrictive deficit (atypical difficulty in using visual and spatial information to guide complex behaviours) was detected, which was associated with changes in molecular and structural brain imaging as well as correlation with upregulation of peripheral immune markers.…”
Section: The Post Covid-19 Condition: a New Disease Framework And Pot...mentioning
confidence: 99%
“…14 A prospective observational cohort study of individuals with polymerase chain reaction (PCR) confirmed SARS-CoV-2 infection and mild COVID-19 presentation examined neurological impairment four months after infection using neuropsychological, ocular, and neurological tests, immune marker assays, structural magnetic resonance imaging (MRI), and 18 FDG-PET neuroimaging. 15 In approximately 25% of individuals, a specific vasoconstrictive deficit (atypical difficulty in using visual and spatial information to guide complex behaviours) was detected, which was associated with changes in molecular and structural brain imaging as well as correlation with upregulation of peripheral immune markers.…”
Section: The Post Covid-19 Condition: a New Disease Framework And Pot...mentioning
confidence: 99%
“…In a study ( de Paula et al., 2022 ) performed with 195 individuals with mild COVID-19, 26% had a visuoconstructive deficiency, a typical early manifestation of Alzheimer’s disease. There was also increased expression of 11 plasma biomarkers, including chemokines and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the volunteers are health professionals who work in the hospital region and learned about the study through advertisements made by the institutions. The mean age of the cohort was 38 years ( de Paula et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the various clinical manifestations of PC19S on the neurological system, some studies have investigated the effect of biomarkers on the central nervous system, such as myelin oligodendrocyte glycoprotein (MOG) and CCL-11 [ 74 ]. In patients with a neurological presentation of PC19S, reactive microglia with astrocyte reactivity, alteration of hippocampal neurogenesis, myelinated axons and oligodendrocytes have been reported in literature [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. In view of this, several mechanisms have been proposed: Cytokine-associated immune dysregulation disrupts myelin hemostasis and plasticity, impairing hippocampal neurogenesis with neurotoxic astrocyte reactivity.…”
Section: Biochemical Diagnosis Of Pc19smentioning
confidence: 99%